Dynamics of geriatric emergency care: comprehensive assessment of emergency medical services utilization and its impact on healthcare resources in coastal India - Vijay Kumar S S; Ananth Prasad Rao H T; Shabbir Shekhli; Anila Jose (Emergency Care Journal)
Emergency Medical Services (EMS) transport significantly influences demographics, admission rates, and mortality among geriatric patients presenting to the Emergency Department (ED). The study evaluated geriatric patients aged 65 years and older, focusing on the impact of transport methods—EMS versus walk-ins—on demographics, admission rates, and mortality outcomes, aiming to identify key areas for improving emergency care delivery for this vulnerable population. Of the total patients, 8.5% were transported by EMS who were predominantly male and more likely to arrive during weekends and nighttime hours. Admission rates were significantly higher in the EMS group, with 30.6% requiring ICU care compared to 5.9% of walk-ins. Mortality rates were also markedly elevated among EMS patients (4.7% vs. 0.3%). The reasons for ED visits varied, with trauma being more frequent in EMS arrivals. This study underscores the critical impact of transport methods on patient outcomes, emphasizing the need to optimize EMS protocols and triage practices. Addressing these factors can enhance care delivery and improve admission and mortality outcomes for geriatric patients in ED settings.